A content analysis of initial proof of life hostage videos released by international terrorist groups. (2nd September 2019) - Rossin, Mark J.; Craun, Sarah W.; Miller, Michelle L.; Collier, Matthew R.
ABSTRACT: After a hostage has been kidnapped and moved to an unknown location, ideologically motivated hostage takers often provide a video demonstrating proof of capture and proof of life. Proof of life videos are one way to establish that a hostage is alive and has been kidnapped. Moreover, the video serves as communication between terrorist hostage takers and the families and also the governments of the hostages. This research is a content analysis of proof of life videos of victims kidnapped by international terrorist organizations. Eighteen proof of life videos, which contained thirty-six hostages and were the first videos released after the kidnappings, were analyzed. Frequencies were run to determine the prevalence of different variables at both the hostage level and the video level. Results show that videos typically only contained one hostage and hostage takers were rarely seen. Physical contact between the hostage takers and hostages was uncommon as was seeing hostages with visible restraints. A majority of the hostages spoke, but the themes of their statements varied widely. Understanding the similarities and differences between proof of life videos across terrorist groups and statements the hostages are allowed or are told to make will enhance the preparation of an operational response.